Differences in Compliance with Depo Medroxy Progeesterone Acetate KB Aceptor Visit Schedules During the Covid 19 Pandemic and the New Normal Period: bahasa indonesia - Fadilah, Nur; Astutik, Heny; yuliani, ita (Jurnal Pendidikan Kesehatan, 2022)
Disobedient Injectable family planning acceptors are one of the causes of the decline in the number of family planning acceptors on the time of the covid 19 pandemic. The purpose of this research is to find out Differences in adherence to DMPA injection family planning acceptor visits schedule pandemic Covid 19 and time new normal. Design study that is study comparative descriptive with a retrospective approach. The analytical test used is the chi square test, the instrument in the study This is the respondent's medical record in the form of a family planning cohort. This research uses 67 respondents were taken with the technique systematic random sampling. Results research out of 67 respondents, most of the respondents are not obedient in doing return visit to COVID 19 pandemic that is as many as 18 respondents and there is 9 respondents who are not obedient in making repeat visits in the new normal. This indicates a decrease in the incidence DMPA injection family planning acceptors are not obedient in making repeat visits to patients the new normal period compared to the COVID 19 pandemic. Conclusion Based on the chi square statistical test, it was found that the p value was 0.019. There were 18 respondents who did not comply during the Covid 19 pandemic, 15 were obedient during the Covid 19 pandemic. Meanwhile, during the new normal period , 25 respondents were obedient in making repeat visits and 9 were not obedient in making repeat visits.